Prevalence of psoriasis in China: a population-based study in six cities - Ding, Xiaolan; Wang, Tinglin; Shen, Yiwei; Wang, Xiaoyan; Zhou, Cheng; Tian, Shan; Liu, Ying; Peng, Guanghui; Zhou, June; Xue, Shuqi; Wang, Renli; Tang, Ying; et al. (EJD. European journal of dermatology, 2012)
Although psoriasis occurs worldwide, the prevalence varies considerably between different peoples and regions. In China, a questionnaire-based study was carried out in 1987 and the prevalence of psoriasis was found to be 0.12%. Since then, no large-scale, population-based study has been reported. To obtain the accurate figures for the prevalence of psoriasis in China. A population-based survey was conducted in 6 cities. The cluster sampling method was used to select communities in each city. The subjects were required to fill out self-reporting questionnaires during a face-to-face interview and also received physical examination by dermatologists. 19,974 subjects were visited and 17,345 completed the questionnaires and received dermatological examination. 102 subjects (0.59%) were found to have psoriasis. After standardization, the prevalence of psoriasis was 0.47%. The prevalence of psoriasis in males and females was 0.54% and 0.44% respectively. 97.06% of the patients had psoriasis vulgaris. 28.43% of the patients reported a family history of psoriasis. 59.80% of patients experienced a negative influence on the quality of life. This population-based and dermatologist-confirmed study showed that the prevalence of psoriasis in China is 0.47%, which is higher than that reported in 1987.